2019
DOI: 10.5114/jos.2019.91234
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mouthguards usage on aerobic capacity of athletes

Abstract: A B S T R AC TIntroduction: The use of intraoral mouthguards is the basic method of preventing injuries of the stomato gnathic system while practicing extreme, contact, team and recreational sports. However, the presence of a protec tive splint in the mouth, especially during exercise, when increased oxygen uptake is needed, may adversely affect the level of blood oxygenation. It is also necessary to compare different types of splint as they differ in retention, size and comfort of usage. Objectives: The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…to not impair overall sports activities and/or performance, [29][30][31] including negligible effects on cardiorespiratory endurance and not impairing ventilatory function. [32][33][34] Some reports suggest that particular SM designs improve physical performance function 27,[35][36][37] and aerobic capacity. 26,38 However, published research overall suggests that SM do not provide superior improvement in general fitness parameters.…”
Section: Sm Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…to not impair overall sports activities and/or performance, [29][30][31] including negligible effects on cardiorespiratory endurance and not impairing ventilatory function. [32][33][34] Some reports suggest that particular SM designs improve physical performance function 27,[35][36][37] and aerobic capacity. 26,38 However, published research overall suggests that SM do not provide superior improvement in general fitness parameters.…”
Section: Sm Compliancementioning
confidence: 99%
“…Non‐compliance with the use of Type 1 and Type 2 SM has been reported 26 due to discomfort, interfering with communication, perceived breathing difficulties, 27,28 and negatively affecting exercise capacity 21 . Conversely, well‐adapted Type 3 SM have been reported to not impair overall sports activities and/or performance, 29–31 including negligible effects on cardiorespiratory endurance and not impairing ventilatory function 32–34 . Some reports suggest that particular SM designs improve physical performance function 27,35–37 and aerobic capacity 26,38 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that improper use of standard/stock and boil-bite may affect some problems such as discomfort, speech, and breathing problems [ 13 , 14 ] and adversely affect exercise [ 15 , 16 ]. On the other hand, it has been reported that a mouthguard specially prepared by a well-adapted dentist does not impair general sports activities and/or performance [ 15 , 17 , 18 ], has a negligible effect on cardiorespiratory endurance, and does not impair respiratory function [ 19 21 ], does not affect speech, does not cause nausea and has a longer service life [ 22 , 23 ]. In the literature, there are some studies which are about the poor level of awareness for the prevention and emergency management of traumatic dental injuries and the use of mouthguards [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%